Administration of Memantine During Withdrawal Mitigates Overactivity and Spatial Learning Impairments Associated with Neonatal Alcohol Exposure in Rats. (15th January 2014) - Idrus, Nirelia M.; McGough, Nancy N. H.; Riley, Edward P.; Thomas, Jennifer D.
<x xml:space="preserve">Abstract</x> Background Prenatal alcohol exposure can disrupt central nervous system development, manifesting as behavioral deficits that include motor, emotional, and cognitive dysfunction. Both clinical and animal studies have reported binge drinking during development to be highly correlated with an increased risk of fetal alcohol spectrum disorders (FASD). We hypothesized that binge drinking may be especially damaging because it is associated with episodes of alcohol withdrawal. Specifically, we have been investigating the possibility that NMDA receptor‐mediated excitotoxicity occurs during alcohol withdrawal and contributes to developmental alcohol‐related neuropathology. Consistent with this hypothesis, administration of the NMDA receptor antagonists MK‐801 or eliprodil during withdrawal attenuates behavioral alterations associated with early alcohol exposure. In this study, we investigated the effects of memantine, a clinically used NMDA receptor antagonist, on minimizing ethanol‐induced overactivity and spatial learning deficits. Methods Sprague–Dawley pups were exposed to 6.0 g/kg ethanol via intubation on postnatal day (PD) 6, a period of brain development that models late gestation in humans. Controls were intubated with a calorically matched maltose solution. During withdrawal, 24 and 36 hours after ethanol exposure, subjects were injected with a total of either 0, 20, or 30 mg/kg memantine. The subjects' locomotor levels were recorded in open field activity monitors on PDs 18 to 21 and on a serial spatial discrimination reversal learning task on PDs 40 to 43. Results Alcohol exposure induced overactivity and impaired performance in spatial learning. Memantine administration significantly attenuated the ethanol‐associated behavioral alterations in a dose‐dependent manner. Thus, memantine may be neuroprotective when administered during ethanol withdrawal. Conclusions These data have important implications for the treatment of EtOH's neurotoxic effects and provide further support that ethanol withdrawal significantly contributes to FASD.